FAKTOR – FAKTOR YANG MEMPENGARUHI LOYALITAS PERAWAT DI RUMAH SAKIT UMUM SEMBIRING DELI TUA TAHUN - Rawalven Purba (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
Loyality of employees at a firm commitment shown by the employees within the company, organizational commitment can be formed due to several factors, namerly of from yourself and the organization the research aims to owing loyality employees at RSU Sembiring Deli Tua. This study used a sample of the entire population of the amount taken as many 95 people as respondents. Research aim to to know Factor - factor influencing Loyalitas Nurse at RSU Sembiring Delitua. Type research of survey have the character of observasional with device of Cross Sectional. Technique intake of sampel with Simple sampling random. This research is executed by month of februari up to May . Population is entire/all nurse which have been lifted to become jobholder that is amounting to 125 people, amounting to 95 People. Research result show there is influence among Salary, Ladder Career, Facility and Medium and also Environmental Environment to nurse loyalitas that is pursuant to Factor Salary ( value p = 0,044), Career ladder factor ( value p = 0,022), Facility factor and Medium ( value p = 0,069), and environmental factor ( value p = 0,061). Data obtained by using kuesioner, analysed with test of Chi Square at examination = 0,05. Research result conclude that which was factor having an effect on to loyalitas in RSU Senbiring Deli Tua that is Factor Employ and leader career. Is expected to researcher here in after to be toimprove the quality of service especially for human resource to through training related to his him. Is suggested to management of RSU Sembiring Deli Tua to strive the make up of officer management quality.